Latihan Relaksasi Secara General terhadap Tingkat Mual dan Muntah pada Pasien Kanker dengan Induksi Kemoterapi - Ningsih, Indarti Dwi; Nuraini, Tuti; Afiyanti, Yati (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of general relaxation exercises on the level of nausea and vomiting in cancer patients receiving chemotherapy induction. The method used in this research is a systematic review of several databases through searches of trusted journals, such as Scopus, EBSCOhost, Springer Link, Proquest and Science Direck, Google Schooler with article analysis using the PRISMA method. The results of the study showed that a total of 10 articles had been analyzed in which there were several relaxation exercise interventions that were given generally and successively proven to reduce the level of nausea and vomiting in cancer patients who received chemotherapy induction. Conclusion: Providing relaxation exercise interventions in general is flexible, simple, easy to learn, and helps reduce the level of nausea and vomiting in cancer patients receiving chemotherapy induction. Keywords: General relaxation exercises, Cancer, Nausea, Vomiting